Nurse Lead Executives: Their Relationship to Health Department Performance, Health Equity Work and the Public's Health - Kett, Paula M (My University, 2021)
Background: Strong public health systems are needed to support optimal population health outcomes. Previous research has demonstrated a positive association between the lead executive with a nursing degree and local health department (LHD) performance. However, the reason for this positive association is unknown, as is whether this positive association translates to reduced inequities in the community. The following parallel mixed methods study addresses this gap by providing valuable information regarding the role and contribution of nurse lead executives to LHD performance and health equity in the community. Methods: Using a national county-level data set with information on LHDs linked to health outcome data, Aim 1 employed a multivariate panel time series design to examine relationships between nurse versus non-nurse lead executives and changes in 15-44-year-old all-cause mortality, infant mortality, and prenatal care in the aggregate as well as Black and White populations (study period 2010-2018, n=626). Aim 2 used multivariate logistic regression and count data analyses to compare nurse and non-nurse lead executives’ engagement in organizational factors important to performance and health equity work (study period 2019, n=1447). Aim 3 used critical thematic analysis of one-on-one semi-structured interviews to explore the specific strategies used by nurse lead executives in LHDs to impact performance and advance health equity (n=13). Results: The first paper found that the nurse lead executive is significantly associated with reduced mortality in the 15-44-year-old Black population (-5.2%, p<0.05), a reduction in the Black-White mortality ratio (-6%, p<0.05) and a reduction in the percent of the population with late or no entry to prenatal care. The second paper suggests that the nurse lead executive, as compared to the non-nurse, is more likely to engage in assessment and planning processes and to emphasize policy activities which are focused on the social determinants of health. Finally, the third paper demonstrates that the nurse lead executive possesses specific skills and competencies, such as capably navigating the political side of their role and approaching their work with an other-focused lens, which support their capacity to achieve success in their leadership role. Conclusions: The results presented here provide a comprehensive understanding of the nursing approach to public health leadership and the importance of that leadership to population health. It demonstrates a distinctive constellation of skills, competencies, and activities which reflect the interprofessional nature of public health nursing practice, demonstrating a specialized approach which may set nurse leaders apart from other types of public health leaders. It also suggests that nurse leaders are associated with health improvements in line with addressing health inequities, further emphasizing the importance of their leadership in work to facilitate health equity.
Thesis (Ph.D.)--University of Washington, 2021
Keywords: Health department performance; Health equity; Nurse leaders; Public health systems; Public policy; Public health; Nursing; Organization theory